2019
DOI: 10.1123/mc.2017-0060
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Declarative Knowledge and Working Memory in Explicit Motor Learning and Practice Among Children With Low Motor Abilities

Abstract: Effective learning methods are essential for motor skill development and participation in children with low motor abilities. Current learning methods predominantly aim to increase declarative knowledge through explicit instructions that necessitate sufficient working memory capacity. This study investigated the roles of declarative knowledge and working memory capacity in explicit motor learning of children with low motor abilities. We studied both acquisition performance (i.e., performance during practice) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…The current findings add important evidence to the increasing body of literature showing a lack, or an unexpected role of working memory for motor learning of children (Brocken, Kal, & van der Kamp, 2016;Jongbloed-Pereboom, Peeters, Overvelde, Nijihuis-van der Sanden, and Steenbergen (2015); Krajenbrink et al, 2018;van Abswoude, Nuijen et al, 2018;van Abswoude, van der Kamp, & Steenbergen, 2018). For example, in a recent study, van van Abswoude, van der Kamp et al, 2018 found only a small effect of visuospatial working memory capacity on performance during practice of an aiming task in an explicit context. However, this effect was not present for retention one day later.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The current findings add important evidence to the increasing body of literature showing a lack, or an unexpected role of working memory for motor learning of children (Brocken, Kal, & van der Kamp, 2016;Jongbloed-Pereboom, Peeters, Overvelde, Nijihuis-van der Sanden, and Steenbergen (2015); Krajenbrink et al, 2018;van Abswoude, Nuijen et al, 2018;van Abswoude, van der Kamp, & Steenbergen, 2018). For example, in a recent study, van van Abswoude, van der Kamp et al, 2018 found only a small effect of visuospatial working memory capacity on performance during practice of an aiming task in an explicit context. However, this effect was not present for retention one day later.…”
Section: Discussionsupporting
confidence: 73%
“…Brocken et al (2016) also failed to show a role for working memory capacity on learning with an internal or external focus of attention, although they only investigated verbal working memory. Finally, in the studies of Krajenbrink et al (2018) and van van Abswoude, Nuijen et al (2018) there was also no role of working memory capacity for respectively learning over a one week period, and performance during practice, with internal or external focus instructions.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It has been argued that implicit learning is advantageous, especially for learners with relatively low motor skills and/or weak working memory. 24,25 However, not all studies confirm this. 26 In addition, implicit learning has been shown to result in enhanced resistance against the adverse effect of stress.…”
Section: Discussionmentioning
confidence: 98%